Glucose promoting the early embryonic development by increasing the lipid synthesis at 2-cell stage - Wang, Mingwen; Xue, Jinfeng; Li, Chanyi; Qi, Lingbin; Nie, Lan; Xue, Zhigang (Frontiers in Cell and Developmental Biology, 2023)
The optimization of culture conditions is one of the main strategies to improve the embryo develeopment competence in in vitro fertilization (IVF). Glucose is an important carbon source while also exists in the oviductal fluid in vivo, the effect of glucose in embryo development microenvironment is still unclear. Here we employed the LC-MS to detect and analyze the metabolites in the culture medium of different cleavage stages including 2-Cell, 4-Cell and 8-Cell mouse embryos, respectively. The effects of the external glucose were estimated by measuring the development rate at different glucose concentrations from 0 mmol/L to 5 mmol/L, and the gene expression changes were detected to explore the potential mechanism after the addition of glucose in the media. Our results indicated the 2-Cell and 8-Cell stages had defined characteristic metabolites, while 4-Cell stage was the transition state. Global and contiguous metabolic characteristics showed the glycometabolism play a critical role at each early cleavage stages during the embryo development. The 8-Cell rates demonstrated the addition of glucose in culture media significantly improve the embryo competence, the highest rate was 87.33% using 3 mmol/L glucose in media, in contrast only 9.95% using the media without glucose. Meanwhile, the blocked embryos were mainly enriched at 2-Cell stage. Further transcriptome study found 3 mmol/L glucose in media remarkably upregulated the gene expression of lipid biosynthesis at 2-Cell stage, the increased lipid was confirmed by nile red staining. These data indicated the glucose may promote the development competence through increasing the lipid biosynthesis to overcoming the 2-Cell block. Our findings were helpful for the further optimization of IVF culture media, as well as the estimation of embryo quality using metabolites in the culture media.